From research to practice: factors affecting implementation of prospective targeted injury-detection systems - Sorensen, A V; Harrison, M I; Kane, H L; Roussel, A E; Halpern, M T; Bernard, S L (BMJ quality & safety, 2011)
AimThis paper describes key factors that shaped implementation of prospective targeted injury-detection systems (TIDS) for adverse drug events (ADEs) and nosocomial pressure ulcers (PrU).MethodsUsing case-study methodology, the authors conducted semistructured interviews with implementation champions and TIDS users at five hospitals. Interviews focused on implementation experiences, assessment of TIDS' effectiveness and utility, and plans for sustainability. The authors used content analysis techniques to compare implementation experiences within and across organisations and triangulated data for explanation and confirmation of common themes.FindingsParticipating hospitals were more successful in implementing the low-complexity PrU-TIDS, as compared with high-complexity ADE-TIDS. This pattern reflected the greater complexity of ADE-TIDS, its higher costs and poorer alignment with existing workflows. Complexity affected the innovations' perceived usability, the time needed to learn and install the trigger systems, and their costs. Local factors affecting implementation and sustainability of both innovations included turnover affecting champions and other staff, shifting organisational priorities, changing information infrastructures, and institutional constraints on adapting existing IT to the electronic TIDS.ConclusionsTo facilitate implementation of complex healthcare innovations such as ADE-TIDS, staff in adopting organisations should give high priority to innovation implementation; allocate sufficient resources; effectively communicate with and involve local champions and users; and align innovations with workflows and information systems. In addition, they should monitor local factors, such as changes in organisational priorities and IT, availability of implementation staff and champions, and external regulations and constraints that may pose barriers to innovation implementation and sustainability.